2021
DOI: 10.3892/mmr.2021.12252
|View full text |Cite
|
Sign up to set email alerts
|

PI3K/AKT phosphorylation activates ERRα by upregulating PGC‑1α and PGC‑1β in gallbladder cancer

Abstract: The nuclear estrogen-related receptor-α (errα) is an orphan receptor that has been identified as a transcriptional factor. Peroxisome proliferator-activated receptor-γ (PParγ) coactivator-1-α (PGc-1α) and PParγ coactivator-1-β (PGc-1β) act as the co-activators of errα. our previous study reported that activated errα promoted the invasion and proliferation of gallbladder cancer cells by promoting Pi3K/aKT phosphorylation. Therefore, the aim of the current study was to investigate whether Pi3K/aKT phosphorylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…PI3K can directly cause phosphorylation of the downstream effector molecule Akt. When the PI3K/ Akt pathway is activated, the Akt phosphorylation level increases, and when the PI3K/Akt pathway is inhibited, the Akt phosphorylation level decreases [30][31][32]. In this study, compared with the model group, the expression levels of PI3K, p-PI3K, Akt, and p-Akt proteins in the tumor tissues of the rats in each group were decreased in a dosedependent manner after afuresertib intervention.…”
mentioning
confidence: 58%
“…PI3K can directly cause phosphorylation of the downstream effector molecule Akt. When the PI3K/ Akt pathway is activated, the Akt phosphorylation level increases, and when the PI3K/Akt pathway is inhibited, the Akt phosphorylation level decreases [30][31][32]. In this study, compared with the model group, the expression levels of PI3K, p-PI3K, Akt, and p-Akt proteins in the tumor tissues of the rats in each group were decreased in a dosedependent manner after afuresertib intervention.…”
mentioning
confidence: 58%
“…The upregulation of PPARG may result from the disrupted lipid balance caused by the inhibition of the PI3K/AKT pathway. It is worth noting that PGC1α , a downstream target of the PI3K/AKT signaling pathway, is positively influenced by the phosphorylated PI3K/AKT signaling pathway, which enhances its activity [ 47 ]. Conversely, when the PI3K/AKT pathway was inhibited, the expression of PGC1α decreased; this conclusion is consistent with the results of our analysis.…”
Section: Discussionmentioning
confidence: 99%
“… 40 PGC1α also acts as the co‑activators of ERRα and activates ERRα via promoting PI3K/Akt phosphorylation to promote the proliferation and invasion of gallbladder cancer cells. 41 Another study in human colorectal cancer revealed that knockdown PGC1α inhibited cell proliferation via the AKT/GSK-3β/β-catenin pathway. 42 …”
Section: Discussionmentioning
confidence: 99%